2018
DOI: 10.1152/ajplung.00365.2017
|View full text |Cite
|
Sign up to set email alerts
|

Akap1genetic deletion increases the severity of hyperoxia-induced acute lung injury in mice

Abstract: Critically ill patients are commonly treated with high levels of oxygen, hyperoxia, for prolonged periods of time. Unfortunately, extended exposure to hyperoxia can exacerbate respiratory failure and lead to a high mortality rate. Mitochondrial A-kinase anchoring protein (Akap) has been shown to regulate mitochondrial function. It has been reported that, under hypoxic conditions, Akap121 undergoes proteolytic degradation and promotes cardiac injury. However, the role of Akap1 in hyperoxia-induced acute lung in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 50 publications
4
29
0
Order By: Relevance
“…In addition to the above-mentioned increases in mitophagy upon AKAP1 deletion under hypoxia conditions, another study demonstrated that hyperoxia conditions also increase mitophagy in AKAP1 KO mice. Following 48 h of hyperoxia treatment, the study found significantly increased PINK1 and Parkin expression in the AKAP1 KO animals, along with elevation of a number of inflammatory cytokines in lung tissue [27]. While this study examined acute lung injury by prolonged exposure to high oxygen concentration and the other studies mentioned above looked at ischemic heart injuries, these studies collectively demonstrate the important role of AKAP1 in preserving mitochondrial functions to promote cell survival under the stressful conditions of both high and low oxygen levels.…”
Section: Akap1 In Cardiovascular Diseasesmentioning
confidence: 85%
See 3 more Smart Citations
“…In addition to the above-mentioned increases in mitophagy upon AKAP1 deletion under hypoxia conditions, another study demonstrated that hyperoxia conditions also increase mitophagy in AKAP1 KO mice. Following 48 h of hyperoxia treatment, the study found significantly increased PINK1 and Parkin expression in the AKAP1 KO animals, along with elevation of a number of inflammatory cytokines in lung tissue [27]. While this study examined acute lung injury by prolonged exposure to high oxygen concentration and the other studies mentioned above looked at ischemic heart injuries, these studies collectively demonstrate the important role of AKAP1 in preserving mitochondrial functions to promote cell survival under the stressful conditions of both high and low oxygen levels.…”
Section: Akap1 In Cardiovascular Diseasesmentioning
confidence: 85%
“…The AKAP1 knockout mouse was generated by deletion of the first coding exon that includes the mitochondrial targeting sequence and the PKA binding site [22]. Even though the AKAP1 knockout mouse was generated over a decade ago [22], a recent flurry of publications has described the use of the AKAP1 gene deletion to tease out the function of AKAP1 in a variety of tissues [23][24][25][26][27][28]. As we begin to discuss the specific roles of AKAP1 in mitochondrial form and function, it is worth noting how the dynamic changes in mitochondrial morphology impact function.…”
Section: Overview Of Akap1: Role In Mitochondrial Fission and Fusion mentioning
confidence: 99%
See 2 more Smart Citations
“…Through regulating ATG7 promoter, OGG-1 links DNA damage with autophagy in stimulating NF-κB–mediated inflammatory response to protect hyperoxia–induced epithelial injury [71]. Hyperoxia also causes a morphological change in mitochondria accomplished with increased expression of mitophagy–associated markers (PINK1 and PARK2) in lung epithelial cells, implying that mitophagy might play a role in protecting epithelial cells from hyperoxia–induced injury [72]. It is worth noting that the hyperoxia–induced ROS accumulation, mitochondrial damage and autophagy were also observed in pulmonary endothelial cells [73,74].…”
Section: The Protective Roles Of Autophagy In Acute Lung Injury (Ali)mentioning
confidence: 99%